Whimsical disclosure evaluating the Ombudsman's policies on access to information in the years 2010-2011 - Patria, Kim Arveen Moreno; Khan, Rachel E. (Quezon City College of Mass Communication, University of the Philippines Diliman, 2011)
"This undergraduate thesis evaluates the policies on access to information enforced by the Office of the Ombudsman, the constitutional anti-graft body of the Philippines, based on the experience of students and journalists. It uses data gathered from students of investigate journalism in the University of the Philippines Diliman and interviews from reporters who covered the Office of the Ombudsman. By identifying the motives behind withholding information or making it public, this study also examines how a government agency that deals with complaints filed against public officials can use its discretion over such information either in favor of the public or to its detriment. This research argues that selective transparency in the Office of the Ombudsman provides opportunities for corruption--by allowing Ombudsman officials to use their power to forward political or economic interest and by perpetuating a culture of impunity in corruption. This study also validates the need for a freedom of information law, which corrects the Office of the Ombudsman's arbitrary policies on access to information."
Thesis (A.B. Journalism)--University of the Philippines Diliman